ONLINE LEARNING ACTIVITIES AND PHYSICS LEARNING OUTCOMES CLASS XI IN GORONTALO CITY HIGH SCHOLL - siswati, puput; Umar, Masri Kudrat; Supartin, Supartin (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine online learning activities in class XI physics learning at Gorontalo City High School, and to determine the results of online learning learning in XI physics learning at Gorontalo City High School. The data analysis used is quantitative descriptive analysis. The results showed that online learning activities in class XI students at SMA Negeri 1 Gorontalo were in the very good category with an average score of 93 at SMA Negeri 3 Gorontalo with an average score of 81 in the good category and at SMA Negeri 4 Gorontalo an average score. 83 in the good category. Online learning for Class XI students at SMA Negeri 1 Gorontalo is in the very good category with an average score of 86, at SMA Negeri 3 Gorontalo with an average score of 75 in the good category and at SMA Negeri 4 Gorontalo an average score of 82 in the good category . The results of online learning in physics learning in class XI obtained an average student learning outcome at SMA Negeri 1 Gorontalo 79 with good criteria, at SMA Negeri 3 Gorontalo 76 with good criteria, and SMA Negeri 4 Gorontalo 75 with sufficient criteria.